The economics of debt management - Scott, Andrew (Henry Stewart Talks, 2009)
The behavior of government debt and its structure, Alternative approaches to debt management, Cost minimization, Risk minimization, The importance of integrating debt management with fiscal policy, How bond market structure influences fiscal policy and debt management, How much insurance do bonds offer?, What is the optimal bond structure, The importance of transaction costs